Use of computed tomography in endodontic diagnosis and planning of maxillary premolar with double radicular curvature (Research, Society and Development, 2021)
Introduction: Imaging exams help in the correct diagnosis and planning of endodontic treatment. Cone beam or cone beam computed tomography (CBCT) is an auxiliary resource in Endodontics, being favorable to the treatment compared to periapical radiography because it allows the evaluation of hard tissues of the maxillofacial region and three-dimensional structures in complex cases, in addition to the possibility of view cut by cut. Objective: To report a clinical case of a patient in need of endodontic treatment in a maxillary premolar with root curvature, being the cone beam computed tomography used as a complementary exam for the evaluation of the root anatomy, diagnosis and planning. Case report: A 37-year-old female patient presents with a fractured tooth with continuous, localized pulsating pain for 6 months. Digital periapical radiographic examination and confirmation by CBCT revealed root dilaceration in the middle third of tooth 15, with double curvature and extensive periapical lesion involving tooth 14. The diagnosis was chronic apical periodontitis in teeth 14 and 15. After 6 months of radiographic and CBCT follow-up, a reduction in the periapical lesion of both teeth submitted to endodontic treatment was observed, with normal clinical characteristics and absence of painful symptoms. Conclusion: CBCT was extremely important for the correct diagnosis, planning and success of endodontic treatment of maxillary second premolars with double root curvature, and should be indicated in the anatomical assessment phase of the patient, as it may be associated with failures in the location, instrumentation and filling of the root canals, compromising the result of the treatment.